Relay zone-based cooperative relaying in multi-user wireless networks. (1st January 2014) - Jia, Nianlong; Feng, Wenjiang; Zhong, Yuanchang
In this paper, a double zone cooperation protocol in a distributed network where nodes individually decide whom to cooperate with without knowing other node's decision is proposed. It answers the key question of how multiple source nodes can form a cooperative pair in a network with good system performance. According to our protocol, the cooperation is achieved in two stages, user zone cooperation stage and relay zone cooperation stage. In the first stage, cooperation is initiated among source nodes with a random selection method or highest SNR selection method. In the second stage, cooperation is designed for those source nodes who fail to get a cooperative partner in the user zone cooperation stage. Both analysis and simulation results show that our proposed protocol achieves full diversity and significant improvement on the packet delivery rate.